KAJIAN HUKUM DALAM PENERAPAN UNDANG-UNDANG TENTANG PENCUCIAN UANG DALAM RANGKA PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA BERBASIS NILAI KEADILAN - Ismaidar Ismaidar; Permai Yudi (Universitas Quality, 2019)
the territorial State. More sophisticated forms of kejahatanya and organized in mess, making it difficult to detect. Criminals are always trying to save money is the proceeds of crime through a variety of ways, one of them by doing money laundering (Money loundering). To be able to apply the law the crime of money laundering, required the existence of a proof of the truth that there has been an act of money laundering, so there are things you need to know before implementing the proof i.e. concept basics of money laundering, money laundering-mode mode, the method of proof is not direct. Criminal acts of corruption is one part of a special criminal law on the side has certain specifications that differ with the general criminal law. such drift event law as well as in terms of the material which is set then the criminal acts of corruption are directly or indirectly intended to suppress the minimal possible occurrence of leakage and irregularities to finance and the economy of the country. This is understandable because on the one hand the development community so quickly and the modus operandi of criminal acts of corruption is more sophisticated and varied while on the other hand the development of the law (law in book) is relatively lagging behind with the development the community. Constraints arising in the investigation of a criminal offence of money laundering can be categorized into two, namely the juridical nature of the constraints and non-juridical. The juridical nature of the obstacle, namely, the existence of the secret provisions of the bank, the liability of the investigator protects reporters and witnesses, the investigator perception against the crime of money laundering has not been perfect, and information from the Transaction reporting and Analysis Centre Finance (PPATK) are not complete. Whereas a non juridical barriers i.e., reporters aren't necessarily victims, and human resources capability Ombudsman is limited